The re-engineering of South African small claims courts - Paleker, Mohamed (Department of Public Law, 2019)
The thesis argues for the retention and reform of the small claims courts. It considers the evolution of the small claims courts since their establishment in 1985, and the steps taken by the Government since 1994 to revitalise the courts to strengthen access to justice. The thesis also considers the management of the courts; the recruitment and qualifications of presiding officers; the rules of jurisdiction and locus standi; the processes and procedures of the courts; and the potential for introducing alternative dispute resolution (mediation). The thesis relies on a broad spectrum of local and foreign literature, the South African common law and statutes, as well as comparative research to argue for the reform of the courts and in particular, the Small Claims Courts Act 61 of 1984 and the Rules Regulating Proceedings in the Small Claims Courts. The small claims courts’ legislation is interrogated and concrete amendments are suggested. Arguments for reform are bolstered by official statistical data sourced from the Department of Justice. The study reveals that significant improvements must be made to the legislation governing the courts. The thesis establishes that the legal rules of jurisdiction and locus standi require a fundamental overhaul. While the thesis is complimentary of certain aspects of the processes and procedures of the courts – for example, the inquisitorial style of conducting a trial and the relaxation of the rules of evidence – it identifies a host of problems that impede access to justice, such as the lack of technology in the courts, cumbersome processes, and the presence of procedures that hinder justice because they are difficult to apply in practice. With regard to the management of the courts, the thesis recommends several steps to improve service delivery and proposes a new organisational framework for court management. The recommendations are easy to implement, with minimum cost to the State. The current regime of recruiting volunteer practitioners to preside in the courts is supported. However, experience shows that there is need to appoint a pool of magistrates to service the courts. In accordance with international trends, mediation in the courts is recommended. The thesis explains how and when mediation should be used to resolve disputes.